2010
DOI: 10.1002/dev.20451
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal amygdala or hippocampus lesions influence responsiveness to objects

Abstract: Medial temporal lobe brain structures, such as the amygdala, play an important role in the normal perception and generation of emotional behavior. Little research, however, has assessed the role of such structures across the neurodevelopmental trajectory. We assessed emotional behavioral responses of rhesus macaques that received bilateral ibotenic acid lesions of the amygdala or hippocampus at two weeks of age and sham-operated controls. At 9 and 18 months of age, animals interacted with novel objects that va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
73
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(86 citation statements)
references
References 23 publications
12
73
1
Order By: Relevance
“…There was a similar maturational change of hostile behavior expression in Neo-Hibo animals, such that there were no group differences during infancy but decreased hostility in adulthood compared to controls. Reduced freezing and hostility during adulthood is consistent with reports of decreased defensive behaviors in monkeys with adult-onset hippocampal lesions (Machado & Bachevalier, 2008; Chudasama, et al, 2008, 2009) and decreased reactivity toward objects in other Neo-Hibo monkeys (Bliss-Moreau, et al, 2010, 2011a). Taken together, these results suggest that early hippocampal damage alters the typical developmental maturation of defensive behaviors, such that animals exhibit decreased defensive behaviors in adulthood.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…There was a similar maturational change of hostile behavior expression in Neo-Hibo animals, such that there were no group differences during infancy but decreased hostility in adulthood compared to controls. Reduced freezing and hostility during adulthood is consistent with reports of decreased defensive behaviors in monkeys with adult-onset hippocampal lesions (Machado & Bachevalier, 2008; Chudasama, et al, 2008, 2009) and decreased reactivity toward objects in other Neo-Hibo monkeys (Bliss-Moreau, et al, 2010, 2011a). Taken together, these results suggest that early hippocampal damage alters the typical developmental maturation of defensive behaviors, such that animals exhibit decreased defensive behaviors in adulthood.…”
Section: Discussionsupporting
confidence: 87%
“…Few studies have shown that neonatal hippocampal damage yields abnormal emotional reactivity to objects and social partners (Bauman et al, 2004; Bliss-Moreau et al, 2010, 2011a, 2013), but normal HPA-axis response to pharmacological challenges assessed at 2.5-4.5 months after the lesion (Goursaud et al, 2006). Yet, none of these studies have investigated the impact of early hippocampal damage on both behavioral and physiological (HPA axis) stress reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…When interacting with novel objects and objects thought to engender threat responding at 18 months of age, amygdala-lesioned animals physically explored objects whereas control animals did not (Bliss-Moreau et al, 2010, Experiment 2), indicating that amygdala-lesioned animals’ affective processing was perturbed in nonsocial contexts. This supports the view that the amygdala is not necessary for social processing per se, but rather serves a broader function related to evaluating threat.…”
Section: Discussionmentioning
confidence: 99%
“…Subject selection and rearing history has been fully described in other publications (Bauman, 2004a, 2004b; Bliss-Moreau et al, 2010; Bliss-Moreau, Toscano, et al, 2011). Briefly, 24 infant rhesus macaque monkeys received bilateral ibotenic acid lesions of either the amygdala (five females, three males) or hippocampus (five females, three males), or sham control operations (four females, four males) at 12-16 days of age.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation